1999
DOI: 10.1002/(sici)1099-1085(19991215)13:17<2931::aid-hyp838>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Application of a conceptual method for separating runoff components in daily hydrographs in Kimakia forest catchments, Kenya

Abstract: Abstract:This paper highlights the use of a conceptual method for separating runo components in daily hydrographs, contrary to the traditionally used graphical method of separation. In the conceptual method, the components, viz. surface¯ow, inter¯ow and base¯ow, are regarded as high, medium and low frequency signals and their separation is done using the principle of a recursive digital ®lter commonly used in signal analysis and processing. It requires estimates of the direct runo (b d ) and surface runo (b s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…In this study, the value of the filter coefficient was carefully chosen based on previous studies which have been compared to either field measurements or traditional hydrograph separation methods. Values of 0.90-0.95 were selected by Nathan and McMahon [44], 0.925 by Arnold et al [1], 0.971-0.985 by Mugo and Sharma [42], and 0.90-0.95 by Eckhardt [16]. Considering that our ultimate goal is the global implementation of the CLMGW model, the digital filter is perhaps the only approach currently suitable for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the value of the filter coefficient was carefully chosen based on previous studies which have been compared to either field measurements or traditional hydrograph separation methods. Values of 0.90-0.95 were selected by Nathan and McMahon [44], 0.925 by Arnold et al [1], 0.971-0.985 by Mugo and Sharma [42], and 0.90-0.95 by Eckhardt [16]. Considering that our ultimate goal is the global implementation of the CLMGW model, the digital filter is perhaps the only approach currently suitable for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…However, Turkey's test revealed that the mean baseflow depth (Qb), interflow depth (Qi) and direct run-off (Qd) from catchment C were significantly higher than those from catchments A (P < 2.2E-03, P < 1.0E-07 and P < 1.0E-03) and M (P < 2.1E-02, P < 3.0E-07 and P < 3.0E-03). As observed by Mugo & Sharma (1999), the undisturbed forest soils in catchment C are covered by organic litter that protects the soil surface and keeps it more permeable to water infiltration, hence the higher baseflow and interflow yield. Indeed, the numerous roots within the soil surface in catchment C would favour preferential flow through macropores, thereby promoting higher storm baseflow and inferflow quantities.…”
Section: Graphically Separated Storm Run-off Componentsmentioning
confidence: 90%
“…Mugo and Sharma [30] showed that the algorithm is capable of producing promising separation results for three humid tropical forested catchments with area from 0.36 to 0.65 km…”
Section: Digital Filtering Processmentioning
confidence: 99%